Speed breeding in pea (Pisum sativum L.), an efficient and simple system to accelerate breeding programs - Cazzola, Federico (2020)
Time in breeding programs is a key factor. Shortening plant cycles allows to increase the efficiency of the programs. The objective of this work is to compare different rapid generation technologies on commercial varieties and then apply the most efficient on two segregating populations in order to develop a simple and low cost speed breeding system in pea. Three methods were evaluated. One completely in vitro that gave very poor results. An in vitro–in vivo system, which shortened the varieties cycles with an intermediate efficiency, and an in vivo method that also shortened the cycles and was selected for its greater efficiency (51–95%) and lower cost. It consisted in a hydroponic system, with a 22-h photoperiod supplied by fluorescent T5 tubes, a temperature of 20 ± 2 °C, flurprimidol antigiberelin and early grain harvest. This method applied to segregating populations presented higher efficiencies than the traditional SSD in the field achieving up to five generations per year. This system called Speed Breeding, includes a simple hydroponic system in a growth chamber, with controlled temperature and photoperiod, flurpimidol antigiberelin and anticipated grain harvesting. Does not require a high investment and allowed to increase the program efficiency significantly, reducing the necessary space (266 plants/m2), the costs and labor.